Wave Analysis Based on Genetic Algorithms Using Data Collected from Laboratories at Different Scales - Cruchaga-Ssa., M; Nunez-Aedo, J (Elsevier Ltd, 2022)
This paper presents the results of a comparative study of waves generated in water channels and in shaking tank systems with the aim of standardizing the use of different laboratories’ facilities and establishing scales for analyzing the evolution of waves under deep water conditions. For this purpose, experimental models are built. The experiments encompass a collection of free surface level measurements obtained from progressive waves in a hydraulic channel and from stationary waves generated by imposing controlled motion to a rectangular tank. The experimental results are also evaluated by contrasting them with analytical correlations. In addition, a model based on a genetic algorithm is proposed to extrapolate the evolution of waves under other physical conditions not measured in the laboratory. The present analysis confirms the viability of wave height comparison between waves generated in a hydraulic channel and those generated by sloshing in a rectangular tank when its natural frequency coincides with the frequency of the progressive wave. Finally, a methodology for establishing a plausible scale for wave comparisons is described and applied. © 2022 Elsevier Masson SAS